Immunological response of live-captured wild elk (Cervus canadensis) to Treponeme-Associated Hoof Disease antigens - Wilson-Welder, Jennifer; Mansfield, Kristin; Han, Sushan; Hoenes, Brock; Alt, David; Humphrey, Sam; Olsen, Steven C. (Frontiers in Veterinary Science, 2026)
A severe hoof disease is affecting wild elk (Cervus canadensis) in the Pacific Northwest. Causing lameness, tissue ulceration and necrosis, hoof overgrowth, and often loss of the hoof itself, bacteria from the genus Treponema are found at the forefront of the lesions. As part of a study evaluating survival and the ability of affected elk to raise young, lymphocytic responses to treponemal antigens were evaluated in live-captured female elk from the endemic area. Serum antibody titers correlated with disease severity and increased antigen-reactive B cells in peripheral blood when compared to healthy or naïve elk. However, we found no evidence that a high antibody titer reduced disease. T lymphocytic responses, CD4+ and CD8+, were mildly proliferative to treponemal antigen, correlating with advanced stages of lesion development. Elk with early-stage lesions also had gamma-delta T cells that proliferated in response to treponeme antigen. Gamma-delta T cells in cattle and sheep have been shown to translocate to the skin preferentially and also have been shown to have a high affinity for spirochete antigens; however, their role in hoof disease of elk or other livestock is not fully understood. In general, initially healthy animals had low lymphocytic responses, indicating that naturally acquired immunity in natural infection is probably rare. Further study is needed to determine the roles of lymphocytes in the protection or perpetuation of these bacteria-driven hoof diseases. In general, immune responses correlated with the severity of disease, with higher responses seen in animals with late-stage disease. No animals were observed with high levels of bacteria responsive immunity in the healthy state, as would be observed if a vaccine or existing immunity was present. Thus, naturally occurring immunity to this disease may be rare. More study is needed to determine the role of immunologically based protection for this and other treponeme-driven hoof diseases.